2019
DOI: 10.1186/s13075-019-1916-9
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept treatment for extended oligoarticular juvenile idiopathic arthritis, enthesitis-related arthritis, or psoriatic arthritis: 6-year efficacy and safety data from an open-label trial

Abstract: Background To describe the 6-year safety and efficacy of etanercept (ETN) in children with extended oligoarticular juvenile idiopathic arthritis (eoJIA), enthesitis-related arthritis (ERA), and psoriatic arthritis (PsA) Methods Patients who completed the 2-year, open-label, phase III CL inical Study I n P ediatric P atients of E tanercep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
(42 reference statements)
10
17
0
1
Order By: Relevance
“…Our analysis included data from 72 patients who completed the ninth year of continuous etanercept treatment. The improvement in disease activity reached in the rst year showed to be maintained during up to nine years of sustained drug use, in accordance to observations from previous studies [22][23]. One third of the patients who had discontinued etanercept treatment due to remission remained in clinical remission off-biologics one year after etanercept withdrawal.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our analysis included data from 72 patients who completed the ninth year of continuous etanercept treatment. The improvement in disease activity reached in the rst year showed to be maintained during up to nine years of sustained drug use, in accordance to observations from previous studies [22][23]. One third of the patients who had discontinued etanercept treatment due to remission remained in clinical remission off-biologics one year after etanercept withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…While other groups have also found higher serious infection rates upon etanercept [3,23] [25]. In our study, herpes zoster reactivation was the only opportunistic infection reported, and it was more often observed in etanercept than in biologic-naïve patients with methotrexate, similarly to what described by others [22][23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While other groups have also found higher serious infection rates upon etanercept [3,24] [25]. In our study, herpes zoster reactivation was the only opportunistic infection reported, and it was more often observed in etanercept than in biologic-naïve patients with methotrexate, similarly to what described by others [23][24].…”
Section: Discussionsupporting
confidence: 89%
“…The comedication with methotrexate, documented in two thirds of the etanercept cohort, may be also a contributing factor, as it was showed in prior studies that serious infections had a higher incidence in patients treated with etanercept-methotrexate combination treatment compared to monotherapy [3]. The rates for serious infections in the etanercept cohort from the BiKeR registry were similar to those reported in other long-term registry studies [19][20], but lower than what described in long-term controlled clinical trials [18,23]. While other groups have also found higher serious infection rates upon etanercept [3,24] [25].…”
Section: Discussionsupporting
confidence: 74%